Potential involvement of nitric oxide synthase but not inducible nitric oxide synthase in the development of experimental corneal neovascularization - Chen, Yuan (International Journal of Ophthalmology Press, 2011)
AIM: To investigate the effect of nitric oxide and its synthetase on experimental corneal neovascularization (CRNV). METHODS: CRNV was induced by alkali injury in mice, nitric oxide synthetase (NOS) was inhibited by NG-nitro-L-arginine (L-NAME) and inducible nitric oxide synthetase (iNOS) was inhibited by aminoguanidine hemisulfate salt (AG). The inhibitory effect was detected at day 2 and 4 after corneal alkali injury by reverse transcription polymerase chain reaction (RT-PCR). CRNV was compared between the control and the treated mice by microscopic observation and corneal whole mount CD31 immunostaining. RESULTS: The inhibition of L-NAME to NOS and AG to iNOS after corneal injury was confirmed by RT-PCR (P<0.05). Compared with control mice, L-NAME treated mice exhibited significantly decreased CRNV areas (P<0.05). In contrast, AG treatment failed to attenuate alkali induced CRNV (P>0.05). CONCLUSION: Our findings suggest that NOS but not iNOS plays a critical role in alkali injury induced CRNV.